Method for Detecting Operation Mistakes with Accelerator Pedal - Tomokazu Suzuki (International Journal of Automotive Engineering, 2018)
Since the sudden acceleration (SA) accidents in the 1980’s, unintended acceleration has been an accelerator pedal operation mistake without a definitive solution. Recent advanced driver assistance system (ADAS) technologies are hoped to save victims from this kind of accident, but their effectiveness is limited. Drivers who have caused this kind of accident have stated that they pressed the brake pedal. An investigation of pedal operation by citizen drivers showed a characteristic action that could be the cause of the accident. This characteristic is also hoped to be an effective method to detect the accelerator pedal operation mistake and prevent unintended acceleration accidents.